COMMUNITY LIFE IN SLUM SETTLEMENT KARYA VII EAST HELVETIA, SUNGGAL SUB-DISTRICT - Yeni Utami Hutasoit; Lister Eva Simangunsong; Rosmaida Sinaga (Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to determine the initial causes of the formation of the Karya VII Helvetia settlement, Sunggal Subdistrict, social and economic life in Karya VII Helvetia settlement, Sunggal District. This research uses a social research approach, by applying field research and assisted by literature in accordance with the discussion. For field research, the authors interviewed 5 people who had lived in Karya VII's settlement for at least 10 years according to the research needs. The data obtained from the results of field research and several literature sources were then analyzed by data reduction, data presentation, and conclusion drawing. From the research results, it is known that the initial cause of the formation of the Karya VII Helvetia settlement in Sunggal Subdistrict was a strong desire to seek a better life in urban areas but this was not accompanied by adequate abilities, which automatically failed to compete in terms of quality. This made them bury their dreams of enjoying a prosperous life, living in a proper place and volunteering to live on land that is not their own or land owned by the State in Karya VII Helvetia, Sunggal District. Economically, in the Karya VII Helvetia settlement, Sunggal Subdistrict, by involving housewives to work as scavengers, traders, using the house yard to raise chickens, using the back of the house to raise pigs.